The politics of visibility in a mined landscape: the image as interface - Hess, Linda (My University, 2016)
Landscape representations in Western art have long stood as metaphors for power relations inscribed on the earth, encoding imperial aspirations, national identity, poetic and aesthetic experiences about humankind, nature and the environment. However, contemporary landscape imagery of large-scale industrial, and particularly mining sites, have come to signify, pre-dominantly through the medium of photography, meta-narratives that go beyond the political, economic, and environmental power relations historically endemic to landscape representation. Indeed, I suggest they constitute the formation of a sub-genre within the category of Landscape. Mining activities characterise extensive landscape interventions, often with catastrophic results both above and below ground. Perhaps a mined landscape more than any other, exemplifies not only the interwoven political and economic power relations inscribed upon the land, but also testifies to the underlying pathology of the land. Contemporary landscape studies cut across disciplines and go beyond the apprehension of surface, taking into account the geological as well social histories of land, and thus signal a shift in the aesthetic experience of land, both emotionally and intellectually, and consequently the way in which land is made visible. The visualisation of these land sites through imagery has precipitated an interface of aesthetic experience that simultaneously makes visible the politics symbolically encoded in the landscape itself, and the politics that impact viewership and reception. Nevertheless, accompanying the need to make visible those land sites hugely modified by mineral extraction, from both a historical and current perspective, is an unprecedented urgency that is weighted by a political anxiety over future implications of such land interventions. This anxiety is driven by the spectral nature of mined landscapes. Although monumental in scale, mined landscapes are often ‘not seen’, partly because they exist in restricted zones or are located underground, but often they are rendered invisible through a process of assimilation and naturalisation. A case in point has been the collective presence of mine dumps along Johannesburg’s southern periphery, and which, now in the process of being re-cycled, form the focus of my selected case study, an image by British photographer, Jason Larkin and titled Re-Mining Dump 20 (2012). By seeking to bring sites of mining activity into public consciousness, contemporary representations of mined landscapes also mediate current relations between humankind and the natural environment. As an agent of mediation, I propose that an image of a mined landscape functions as an interface. By situating Larkin’s image within a theoretical framework motivated by Jacques Rancière’s politics of aesthetics and Malcolm Andrews and W.J.T. Mitchell’s landscape theory, I proceed with my investigation in the form of a two-part interrogation: one that places emphasis on theory followed by a practical, creative response to Larkin’s image by way of repeat photography of Dump 20 and its surrounds. To demonstrate the concept of interface, I ‘excavate’ the aesthetic experience of Dump 20 as both sensory apprehension and through Rancière’s lens of emancipated viewership. There is an aesthetic quality of the sublime that appears to pervade visual representations of mined landscapes. Described as industrial sublime, toxic sublime or even apocalyptic sublime, the attention-holding quality these images exercise, through a strategy of aesthetic appeal, contribute to a politics of visibility by subversively implicating the viewer as a member of the human race. Global citizenship overrides national identity in these landscape representations, disrupting a sense of belonging with one of complicit participation in the formation of mined landscapes through reliance on mineral extraction for manufacturing consumer goods. Not only do representations of mined landscapes demand a rethink about aesthetic appreciation of landscape imagery and the endemic political connotations implicated in an understanding of landscape. They actively seek to penetrate surface visibility of land by taking into account the very pathology of land as an on going narrative of human and environmental interaction and life continually in process.
University of the Witwatersrand Masters Research Report History of Art 31 March 2015
Keywords: Landscape photography--South Africa; Landscape photography--Exhibitions; Land use--Political aspects--South Africa--History